COMPARATIVE STUDY OF ANTIBACTERIAL ACTIVITY OF TWO DIFFERENT TYPES OF HONEY AGAINST Escherichia coli, Pseudomonas aeruginosa AND Staphylococcus epidermidis - Khudair, Mohammed K.; Qassim, Ammar R. (Diyala Agricultural Sciences Journal, 2010)
This study aimed to investigate the antibacterial activity of two different types of honey, natural and commercial, by determination the minimum inhibitory concentration (MIC) against isolates of Staphylococcus epidermidis, E.coli and Pseudomonas aeruginosa. In this study, fifty eight (58) human isolates of these organisms were collected from different pathological sources from both males and females with age between (9-50) years and tested for their sensitivity to honey, a natural product that is generating renewed interest for its therapeutic application, during the period from 30/10/2009 to 1/4 /2010. In a tube dilution method, the incidence rate of bacterial inhibition was always significantly higher when natural honey was used compared to commercial honey at the three successive dilutions tested. At the highest concentration tested (1:2 dilution) all the bacterial isolates tested where inhibited (100%) by both types of honey tested. The median MIC was significantly lower for E.coli than Pseudomonas aeruginosa and Staphylococci epidermidis when exposed to commercial honey. The median MIC causing bacterial inhibition and mean rank was always significantly lower for natural honey compared to commercial honey in all the three types of bacterial isolates.